RAJA RAO’S KANTHAPURA: A STUDY IN THE LIGHT OF INDIAN ORAL TRADITIONS - Tiwari, Iti; Mudgal, Abhay (International Journal of Research -GRANTHAALAYAH, 2025)
Indian writers have significantly impacted literature worldwide by offering new perspectives and compelling stories to people globally. Authors such as Rushdie, R.K. Narayan, and Rabindranath Tagore have brought Indian stories and personalities to life through their works, infusing them with the rich flavours and textures of Indian culture. Raja Rao significantly contributed to the development of the English novel in India. He skillfully fictionalises the diverse socio-cultural, economic, and interpersonal interactions of different people. These elements of Indian ethos include religiosity and spirituality. Achakka, a character in the novel, narrates how Kanthapura assimilates the oral traditions seen as deeply rooted in the Indian knowledge system. This paper highlights Rao’s narrative techniques and how he uses oral traditions to portray India's freedom struggle. Further, the paper intends to explore Raja Rao’s Kanthapura as a narrative rooted in Indian oral tradition. It emphasises how Moorthy uses Harikatha and Bhajans to unite people and fight for independence. This paper attempts to establish how Raja Rao used oral traditions that were deeply rooted in Indian society and played a significant role in India's freedom struggle.